FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN MINAT PETANI KENTANG UNTUK MENABUNG DI BANK SYARIAH KECAMATAN PANGALENGAN KABUPATEN BANDUNG - Ega Yunita Sari; Eliana Wulandari (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Sharia banks are part of Islamic financial institutions that offer services as funding. Farmers can participate in accessing facilities from Sharia banks. Pangalengan District is an area known for the agricultural products, namely potatoes. The majority of the population works as farmers. Saving carried out by potato farmers in sharia banks are still low, farmers are saving more in conventional banks. Farmers’ interest in saving in sharia banks can be influenced by several factors. This study aimed to determine the factors related to the interest of potato farmers’ to save in sharia banks in Pangalengan District. This research used survey method using quantitative descriptive data and multiple linear regression analysis. This research indicated that services, knowledge, farming income, and promotion are significantly related to the interest of potato farmers' to save in sharia banks in Pangalengan Sub-District, Bandung District.